2020
DOI: 10.1002/eat.23247
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and eating disorder psychopathology: A meta‐analysis

Abstract: Objective: Mindfulness is implicated in eating disorder (ED) psychopathology. However, this literature has not been synthesized to date. The current meta-analysis examined the associations between mindfulness and ED psychopathology.Methods: A total of 74 independent samples (effects = 576) were included. We used a multilevel random-effects model to estimate summary study-level effect sizes, and multilevel mixed-effects models to examine moderator effects.Results: Mindfulness was negatively associated with ED p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 86 publications
6
35
0
7
Order By: Relevance
“…Indeed, mindfulness has been associated with decreased symptom severity in people who engage in negative emotional eating (Alberts et al, 2010; Daubenmier et al, 2011) and BE (Baer et al, 2005; Kristeller & Hallett, 1999). A recent meta‐analysis demonstrated that across the full spectrum of eating pathology, mindfulness appears to be especially useful in symptom reduction of negative emotional eating and BE (Sala et al, 2020). In treatment contexts, mindfulness meditation interventions such as mindfulness training was associated with decreased negative emotional eating and BE across diverse overweight/obese and clinical eating disorder populations (Katterman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mindfulness has been associated with decreased symptom severity in people who engage in negative emotional eating (Alberts et al, 2010; Daubenmier et al, 2011) and BE (Baer et al, 2005; Kristeller & Hallett, 1999). A recent meta‐analysis demonstrated that across the full spectrum of eating pathology, mindfulness appears to be especially useful in symptom reduction of negative emotional eating and BE (Sala et al, 2020). In treatment contexts, mindfulness meditation interventions such as mindfulness training was associated with decreased negative emotional eating and BE across diverse overweight/obese and clinical eating disorder populations (Katterman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness, however, refers to 'awareness of one's internal states and surroundings' (American Psychological Association, n.d.). Although mindfulness does share overlapping elements with flow state, such as a here-and-now focus, they are quite different (Lambert & Csikszentmihalyi, 2020;Sala et al, 2020).…”
Section: Definition Of Flow Statementioning
confidence: 99%
“…Mindfulness involves people engaging in a process demanding selfdiscipline and a dedication to continuously reflect and be aware of themselves and the world around them (Hill et al, 2020;Sala et al, 2020). This consciousness could entail being attuned to nature and one's own biological mechanisms (e.g., breathing) concurrently.…”
Section: Definition Of Flow Statementioning
confidence: 99%
“…They aim to cultivate a non-judging awareness of experiences in the present moment and promote greater self-regulation (Brown et al, 2007). General mindfulness-based interventions reduce stress reactivity (Hoge et al, 2013) and emotional and binge eating (Sala et al, 2020). Recent cross-sectional work suggests that acting with mindful awareness weakens associations between emotional and binge eating severity (Barnhart et al, 2021).…”
mentioning
confidence: 99%